The Role of School Principals to Improve Teacher Professionalism in Indonesia: A Systematically Literature Review - Mubin, Holikul; Muhayani, Ulfah; Syahputri, Ghifari Sasmita Mutiara Ayu; Ahnaf, Sherly Amanda; Amrullah, Mohammad Haekal Izzat (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
This study aims to analyze the role of school principals in improving teacher professionalism in Indonesia through a systematic review method. The data was gathered from various indexed sources, including Google Scholar, Publish or Perish indexed by PubMed, Crossref, and Semantic Scholar, using keywords such as